FDI Spillovers Over Time in an Emerging Market: The Roles of Entry Tenure and Barriers to Imitation - Zhang, Yan “Anthea”; Li, Yu; Li, Haiyang (Academy of Management Journal, 2014)
In this study, we examine how foreign direct investment (FDI) spillovers to domestic firms in an emerging market occur over time. From the organizational learning perspective, we propose that, as entry tenure of foreign firms in an industry increases, domestic firms can learn from the foreign firms over time and improve their productivity. We further build upon the competitor imitation argument to propose that this effect will be stronger when barriers to imitation faced by the domestic firms are lower. Based upon a comprehensive panel dataset on manufacturing firms in China in 1998–2007, our findings strongly support these arguments. We find that entry tenure of foreign firms in an industry has a positive relationship with the productivity of individual domestic firms in the same industry, albeit at a diminishing rate. We also find that this positive relationship is stronger when the foreign firms have lower export intensity, lower intangible asset intensity, and have followed a more rhythmic (i.e., less irregular) entry pattern—situations characterizing lower barriers to imitation.